Hemostatic effect and safety evaluation of oxidized regenerated cellulose in total knee arthroplasty- a randomized controlledtrial - Bowei Li; Wenjie Pan; Xiaobo Sun; Kai Qin; Guoyang Bai; Huanli Bao; Yuanchi Huang; Jianbing Ma (BMC Musculoskeletal Disorders, 2023)
Abstract Background Oxidized regenerated cellulose (ORC) is a type of biodegradable hemostatic material, which has been widely used in the field of surgery. However, its hemostatic effect in patients undergoing total knee arthroplasty (TKA) is uncertain. Accordingly, this study investigated the effectiveness and safety of ORC in patients receiving TKA. Methods Seventy patients undergoing unilateral TKA were randomized into blank control group and ORC (2 pieces of ORC placed in the joint cavity) groups. Then, the two groups were compared for primary (perioperative blood loss [total blood loss, intraoperative blood loss, and hidden blood loss] and hemoglobin drop values) and secondary (coagulation indicators, inflammatory indicators,operation time, and complication rates) outcomes. Results The total blood loss in the ORC group was 902.32 ± 307.82 mL, which was statistically significantly lower than that in the control group (1052.25 ± 308.44 mL) (P < 0.05). Postoperative hidden blood loss was also statistically markedly lower in the ORC group (801.61 ± 298.80 mL) than in the control group (949.96 ± 297.59 mL) (P < 0.05). There was no significant difference between the two groups in terms of coagulation indicators, inflammatory indicators, operation time, and complication rates. Conclusion In conclusion, our prospective RCT study proved that regenerated oxidized cellulose can be used safely in vivo and can effectively reduce postoperative blood loss in patients, which is a potential method for preventing blood loss after TKA. Trial registration This prospective RCT was reviewed and approved by the Ethics Committee of Honghui Hospital of Xi’an Jiaotong University (No: 202,211,007) and was designed and conducted according to the rules of the Declaration of Helsinki. Written informed consent was obtained from patients or their legal guardians.